2010
DOI: 10.1016/j.arbres.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Papel de los receptores toll-like en las enfermedades respiratorias

Abstract: There has been growing interest in the last 10 years in the study of innate immunity, in particular because of the possible role that toll-like receptors (TLR) may play in the pathogenesis of some respiratory disease such as for example, asthma, chronic obstructive pulmonary disease, and infections. TLR are a family of type 1 transmembrane proteins, responsible for recognizing molecular patterns associated with pathogens (PAMP, pathogen-associated molecular patterns), and expressed by a broad spectrum of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 95 publications
0
8
1
Order By: Relevance
“…TLRs are single transmembrane pattern recognition receptors that recognize molecules derived from various pathogens, referred to as pathogen-associated molecular patterns (PAMPs) (Crespo-Lessmann et al, 2010Delgado et al, 2008Esen and Kielian, 2006Chalifour et al, 2004Tobian et al, 2003) . TLRs are highly conserved from invertebrates to mammals, and are essential for mediating innate immunity and the production of cytokines in response to infectious agents (O'Neill, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…TLRs are single transmembrane pattern recognition receptors that recognize molecules derived from various pathogens, referred to as pathogen-associated molecular patterns (PAMPs) (Crespo-Lessmann et al, 2010Delgado et al, 2008Esen and Kielian, 2006Chalifour et al, 2004Tobian et al, 2003) . TLRs are highly conserved from invertebrates to mammals, and are essential for mediating innate immunity and the production of cytokines in response to infectious agents (O'Neill, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the ligation of Toll-like receptors (TLRs) by bacterial or viral antigens can affect IgE-dependent mast cell degranulation and release of preformed mediators, as well as eicosanoid production, thus providing evidence on the involvement of innate immunity in the pathogenesis of asthma [ 2 5 ]. Among the various agents involved in innate immunity in the pathogenesis of asthma, the TLRs may bear an important role [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Just because these receptors are expressed on the cellular surface makes them easy to measure. Our laboratory has expertise in measuring them [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ENX signal is recognized predominantly through interaction with TLR4. TLR2 can recognize some atypical LPS [ 33 ] as long as peptidoglycans or PGN and lipopeptides derived from Gram-positive bacteria and fungal molecules [ 34 ]. Both receptors activate cellular events that lead to the recruitment of specific adaptor molecules.…”
Section: Introductionmentioning
confidence: 99%